Impact of artificial coastal protection structures on Ascidians settlement along the Tamil Nadu coast, India - Prince Prakash Jebakumar Jebarathanam; Nandhagopal Ganesan; Rajan Babu Bose; Ragumaran Shunmugavel; Ramakritinan Chokalingam Muthiah; Abdul Jaffar Ali; Mohammed Kaleem Arshan; Vijaya Ravichandran (Oceanologia)
Summary: Ascidians are one of the dominant marine sedentary filter feeders recorded more frequently as introduced species than other taxa. It is renowned that artificial structures offer novel niches to the non-native species. A yearlong investigation was carried out to understand the role of ascidian colonization on various artificial structures located along 84 stations stretched on the 1076 km long Tamil Nadu coast of South India. It revealed the occurrence of 26 ascidian species, among these18 specimens were identified to species level, 8 were identified to genus level based on morphological characters. As on origin and nativity, out of the total 26, 3 species were classified as introduced, 8 species were classified as native and 15 as cryptogenic species. Interestingly, Polyclinum isipingense and Diplosoma variostigmatum were reported first time in Indian waters. The cryptogenic and colonial forms of ascidians are dominant in the artificial structures. There were significant differences observed between artificial structure type, geographic locations (p = 0.0071) and between ascidians forms as well as geographic areas (p = 0.00375). This study also confirms the artificial structures offer new niches for non-native ascidian colonization. The influence of the substrate (structure type) as well as geographic locations on the biotic assemblage was also observed. Keywords: Artificial structures, Novel niche, Ascidian, Native, Introduced, Cryptogenic